Clonal analysis for elucidating the lineage potential of embryonic NG2+ cells - Ju, Peijun (2013)
Background aims. The widespread NG2-expressing neural progenitors in the central nervous system (CNS) are considered to be multifunctional cells with lineage plasticity, thereby possessing the potential for treating CNS diseases. Their lineages and functional characteristics have not been completely unraveled. The present study aimed to disclose the lineage potential of clonal NG2+ populations in vitro and in vivo. Methods. Twenty-four clones from embryonic cerebral cortex-derived NG2+ cells were induced for oligodendrocyte, astrocyte, neuronal and chondrocyte differentiation. The expression profiles of neural progenitor markers chondroitin sulfate proteoglycan 4 (NG2), platelet-derived growth factor-α receptor (PDGFαR); nestin and neuronal cell surface antigen (A2B5) were subsequently sorted on cells with distinct differentiation capacity. Transplantation of these NG2+ clones into the spinal cord was used to examine their lineage potential in vivo. Results. In vitro differentiation analysis revealed that all the clones could differentiate into oligodendrocytes, and seven of them were bipotent (oligodendrocytes and astrocytes). Amazingly, one clone exhibited a multipotent capacity of differentiating into not only neuronal–glial lineages but also chondrocytes. These distinct subtypes were further found to exhibit phenotypic heterogeneity based on the examination of a spectrum of neural progenitor markers. Transplanted clones survived, migrated extensively and differentiated into oligodendrocytes, astrocytes or even neurons to integrate with the host spinal cord environment. Conclusions. These results suggest that NG2+ cells contain heterogeneous progenitors with distinct differentiation capacities, and the immortalized clonal NG2+ cell lines might provide a cell source for treating spinal cord disorders.